Gold and Prices Since 1873 - Laughlin, J. Laurence (Quarterly Journal of Economics, 1887)
Gold and Prices since 1873 J. Laurence Laughlin J. Laurence Laughlin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 3, April 1887, Pages 319–355, https://doi.org/10.2307/1882761 Published: 01 April 1887